Significance of Anisotropic Thermal Expansion in High Speed Electric Machines Employing NdFeB Permanent Magnets - Ram Kumar (MDPI AG, 2021)
Many high speed applications employ a surface permanent magnet (PM) machine topology with a retaining sleeve due to its robustness and ability to achieve high overall peripheral speeds as well as efficiencies. One often overlooked feature in the mechanical design of such machines, which has not achieved sufficient attention to date is the anisotropic thermal expansion of rare earth magnets, the degree of which varies for different magnet technologies. This paper investigates the effects of the aforementioned on the mechanical design of a high speed PM spindle machine with NdFeB magnets. The maximum allowable interference is found to be limited by the working temperature of the magnets while the minimum required interference is increased due to their anisotropic thermal expansion. Based on this, appropriate conditions are formulated to integrate a Neodymium Iron Boron (NdFeB) PM in high speed rotors. These modifications considering the shaft together with the magnet anisotropic thermal expansion are included in a proposed rotor design and validated using simulations in ANSYS mechanical environment.